Examining the Impact of Structured, Reflective Prebriefing on Student Performance During Simulation. Issue 6 (3rd November 2022) - Watts, Sarah O.; Curtis, Amy; Ware, Katilya S.; Chidume, Tiffani; Jones, Meghan C.
Abstract: Little is known about the impact of prebriefing on students' experiences of learning with simulation. This mixed-methods study evaluated the impact of prebriefing activities on nursing students' satisfaction, confidence, and performance of nursing skills during a simulation. Findings revealed students who experienced a structured, more robust prebriefing had improved performance during the simulation and reported higher levels of confidence and satisfaction in learning compared to a group that experienced a standard prebriefing. Findings are significant to the profession, they support the incorporation of structured, reflective prebriefing activities in simulation-based experiences.